Diagnosis and management of HELLP syndrome at a Peruvian hospital - Zapata Díaz, Betsy Micol (2020)
Introduction: HELLP syndrome is characterized by hemolysis, elevated liver enzymes, and thrombocytopenia; it is one of the most serious maternal complications of pregnancy, with significant morbidity and mortality, and high risk of renal failure, hepatic hematoma, disseminated intravascular coagulopathy and receiving multiple blood transfusions. Objective: To describe the clinical presentation, diagnosis, complications and management of patients with HELLP syndrome in a Peruvian hospital. Method: Descriptive, retrospective study of cases with HELLP syndrome at a Peruvian hospital. Results: Out of 30 618 deliveries, 71 cases of HELLP syndrome were found, with an incidence of 0.23%; 68% of cases were multiparous, with an average age of 33. Diagnosis was confirmed during pregnancy in 46% (58% of them developed HELLP syndrome before 37 weeks of gestation) and in the puerperium in 54%. Maternal morbidity included renal failure in 25%, hepatic hematoma with or without rupture in 11%, respiratory failure in 7%, eclampsia in 6%; patients required platelets or blood products transfusions in 85% of cases. Maternal mortality was 3%. Conclusions: In the population studied, HELLP syndrome was associated with high maternal morbidity. Maternal death was mainly due to liver hematoma or eclampsia. Key words: HELLP syndrome, Preeclampsia.